2008
DOI: 10.1002/mnfr.200700266
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary habits and mycotoxin occurrence in human mature milk

Abstract: During 2006, 82 samples of human mature milk were collected at Italian hospitals and checked for aflatoxin M1 (AFM1) and ochratoxin A (OTA) by immunoaffinity column extraction and HPLC. AFM1 was detected in four (5%) of milk samples (ranging from < 7 ng/L to 140 ng/L; mean level: 55.35 ng/L); OTA was detected in 61 (74%) of milk samples (ranging from < 5 ng/L to 405 ng/L; mean level: 30.43 ng/L. OTA levels were significantly higher (p less, not double equals 0.05) in milk of habitual consumers of bread, bakery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 19 publications
(16 reference statements)
2
49
0
Order By: Relevance
“…The present results are comparable with those obtained by Turconi et al (2004) and Galvano et al (2008) in two studies regarding human milk performed in Italy (198 of 231 samples contaminated with 1-57 ng/L and 74 of 82 samples contaminated with < 5 ng/L-405 ng/L, respectively), while are lower than those reported by Micco et al (1991;1995) (ranges 1700-6600 ng/L and 100-12000 ng/L, respectively).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The present results are comparable with those obtained by Turconi et al (2004) and Galvano et al (2008) in two studies regarding human milk performed in Italy (198 of 231 samples contaminated with 1-57 ng/L and 74 of 82 samples contaminated with < 5 ng/L-405 ng/L, respectively), while are lower than those reported by Micco et al (1991;1995) (ranges 1700-6600 ng/L and 100-12000 ng/L, respectively).…”
Section: Resultssupporting
confidence: 83%
“…OTA was detected in 198 samples (85.7%) at an average value of 6.01 ng/L. More recently, data from milk samples collected from 82 Italian women indicated that 74% of human milk samples contained OTA in the range < 5 ng/L-405 ng/L (Galvano et al, 2008). In the same study AFM1 was detected in four (5%) of milk samples (ranging from < 7 ng/L to 140 ng/L) (Galvano et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was reported that, in Egypt, 36% of breast milk samples had 5000-45 000 ng l −1 OTA (AbdAlla et al, 2002) and in Sierra Leone 35% of the samples contained OTA ranging from 200-337 000 ng l −1 (Jonsyn et al, 1995). Recently, Galvano et al (2008) reported that OTA was detected in 74% of breast milk samples ranging from <5 to 405 ng l With regard to its widespread distribution and continuous exposure of human population to OTA, and in addition to its determined wide range of toxic eff ects in animals, studies about the evaluation of its unwanted eff ects in humans is a necessity. According to current methods, complete avoidance of OTA contamination in foodstuff s is not yet possible (Clark and Snedeker, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Obviously, breast milk OTA contamination is related to maternal dietary habits, which may vary from country to country. In Italy, significantly higher OTA concentrations in breast milk correlate with the consumption of bread, bakery products, and pork meat (36), while in Norway they correlate with the consumption of liver paste (liverwurst, liver paté) and cakes (cookies, fruitcakes, chocolate cakes) (86). An Egyptian study (78) looked at a number of biochemical parameters in blood and urine of breast-fed children with high and low levels of OTA in maternal milk and children's blood.…”
Section: Aflatoxinsmentioning
confidence: 99%